Estrés Laboral asociado al desempeño profesional enfermero. Servicio emergencia. Hospital de Especialidades Abel Gilbert Pontón. Periodo Marzo- Julio 2024. - Guerrero Rivadeneira, Ariana Gabriela (2024)
Emergency service nursing professionals face numerous stressors that can influence their work performance, affecting the quality of patient care; aim; determine the stress levels associated with the performance of the nursing professional; methodology; level and cross-sectional correlational descriptive design; The population consisted of 30 nursing professionals from the emergency service; The level of performance was measured through the SPSS perceived stress scale with an acceptable McDonald's Omega index and Cronbach's alpha of 0.70; job performance questionnaire with an acceptable Cronbach's Alpha test coefficient of 0.86; results; indicate that moderate levels of stress occur in 70% of cases, while high levels of stress occur in 20%. Regarding professional performance, 83.3% are at a high level of performance and 16.7% correspond to the average level. The Spearman rating indicates that the significance value p= 0.119 > 0.05, therefore, the alternative hypothesis is rejected and the null hypothesis is accepted, that is, work stress is not associated with the performance of the nursing professional; concludes; There is no statistically significant relationship between the stress variables and job performance. As a contribution, a coping workshop was held with professionals in the area measured by questionnaire with criteria of usefulness, clarity,relevance and applicability. The results demonstrated 100% satisfaction regarding usefulness, clarity, greater than 66% in relevance and applicability.